Effect of Microemulsions of Essential Oils on Human Erythrocyte and Pathogens Bacteria - López, M. A.; Valbuena Gregorio, E.; Quihui Cota, L.; Morales Figueroa, G. G.; Ruiz Cruz, S.; Campos García, J.; Díaz Meza, E.; Pablos Rodríguez, D. E. (Revista Mexicana de Ingenieria Biomedica, 2017)
The aim of the study was to evaluate the effect of microemulsions of rosemary (AER) and tea tree (AET) essential oils on human erythrocyte and pathogen bacteria. Microemulsions of each oil were prepared at 8.0% (v/v), 5.0% (v/v) and 2.5% (v/v), and they were tested on human erythrocyte to determine the hemolysis percentage, hemolysis inhibition percentage and the antibacterial capacity against E. coli O157:H7 and S. aureus. All AER microemulsions showed no significant hemolytic activity. On the contrary, AET microemulsions showed hemolytic effect but those in concentrations of 8.0% (≈70%) and 5.0% (33%) showed the highest effect. In addition, AER microemulsions showed protective effect against free radicals in comparison with the AET microemulsions (p<0.05). On the other hand, the AET microemulsion at 8.0% showed antibacterial effect against E. coli O157:H7 and S. aureus, and the AER at 8.0% showed antibacterial effect against E. coli O157:H7. The limitation of this study was that nucleated cells were not used to observe the damage of the essential oils on nuclear material. However, the observed damage of erythrocyte’s membrane is depending on type and amount of used oil. Therefore, it can be concluded that the AER microemulsions showed better protective effect of erythrocytes, while AET microemulsions showed better antibacterial effect against the tested bacteria, although with toxic effect on the erythrocytes.